The Relationship of Lean Body Mass with Vitamin D Level and Physical Performance - Eylül Yağıcıbulut Eren; Selda Sarıkaya; Şenay Özdolap (Galenos Yayinevi, 2019)
Objective:In this study, it was aimed to investigate the association between vitamin D level, physical performance and lean body mass (LBM).Materials and Methods:A hundred female patients with 35-50 age range were included in the study. Patients' demographic variables, height and weight measurements were recorded and body mass index (BMI) was calculated. Serum 25-hydroxyvitamin D (25(OH)D) samples were analyzed. Patients were divided into 2 groups according to 25(OH)D levels; patients with low vitamin D levels (group 1) and normal vitamin D levels (group 2). Both groups' LBM was assessed by dual-energy X-ray absorptiometry and physical performance was assessed by 6-Minute Walk Test (6MWT).Results:Mean levels of 25(OH)D were found as 14.026±7.10 ng/mL in group 1 and 43.40±10.03 ng/mL in group 2. When the results of LBM were evaluated, the mean of group 1 was 35.48 (26.33-47.17) kg and the group 2 was 35.14 (29.23-53.65), and there was no statistically significant difference between the groups with regard to the mean of LBM (p=0.679). No statistically significant difference was determined in terms of 6-MWT (p=0.992). According to serum 25(OH)D level, group 1 was divided into three subgroups as follow; Group 1a: 25(OH)D<10 ng/dL, group 1b: 10.1≤ 25(OH)D≤ 20 ng/dL, and group 1c: 20.1≤25(OH)D≤29.9 ng/dL. When the three subgroups of group 1 (group 1a, 1b, and 1c) and group 2 compared, there was no statistically significant difference observed between the LBM and 6-MWT means (p=0.975; p=0.644).Conclusion:In this study, we could not determine a relationship between LBM and serum 25(OH)D level, and physical performance. In patients with same exclusion criteria, we believe that it is necessary the studies evaluating on the serum 25(OH)D levels along with genetic factors influencing the functions of vitamin D and also on the muscle quality along with muscle mass.